An improved finite-set model predictive current control for 3L-HANPC inverter fed PMSM drives - Kim, Seok Min; Lee, Kyo Beum (ITEC Asia-Pacific 2019 - 2019 IEEE Transportation Electrification Conference and Expo, Asia-Pacific: New Paradigm Shift, Sustainable E-Mobility, 2019)
This paper proposes an advanced finite-set model predictive current control (FS-MPCC) for permanent magnet synchronous motor (PMSM) drives fed by three-level hybrid active neutral point clamped (3L-HANPC) inverter. The 3L-HANPC which is state of the art in multilevel topology provides outstanding performances in terms of system efficiency and thermal behavior of switching devices in bi-directional power delivery. Computational burden is a major hurdle for practical implementation of FS-MPCC of motor drive. To reduce the huge computation and calculation time, the optimal section is determined thus the number of voltage vectors is selected and the calculation time for cost function can be reduced. Simulation results confirm that the computation burden could be reduced while dynamic performance is comparable with the conventional all voltage-vectors based FS-MPCC.
Keywords: Active neutral point clamped; Active npc; Computational burden; Execution time; Model predictive; Motor drive; Multilevel topologies; Permanent magnet synchronous motor drives; Active NPC inverter; Deadbeat zone; Execution time; Model predictive current control; Motor drive